Expanded and Independent Spanish Validation of the MDS‐Non Motor Rating Scale. Issue 4 (13th March 2023) - Cubo, Esther; Luo, Sheng; Martínez‐Martín, Pablo; Stebbins, Glenn T.; Lin, Jeffrey; Choi, Dongrak; García‐Bustillo, Alvaro; Mir, Pablo; Santos‐Garcia, Diego; Serrano‐Dueñas, Marcos; Rodriguez‐Violante, Mayela; Singer, Carlos; et al.
Abstract: Background: The Movement Disorder Society‐sponsored Non‐motor Rating Scale (MDS‐NMS) assess the severity and disability caused by non‐motor symptoms (NMS) in Parkinson's disease (PD). Objective: This article encapsulates the formal process for completing this program and the data on the first officially approved non‐English version of the MDS‐NMS (Spanish). Methods: The MDS‐NMS translation program involves four steps: translation and back‐translation; cognitive pre‐testing to ensure that raters and patients understand the scale and are comfortable with its content; field testing of the finalized version; analysis of the factor structure of the tested version against the original English language version for the nine domains that could be analyzed in a confirmatory factor analysis. To be designated an "Official MDS translation, " the confirmatory factor analysis Comparative Fit Index had to be ≥0.90. Results: The Spanish MDS‐NMS was tested in 364 native‐Spanish‐speaking patients with PD from seven countries. For all subjects with fully computable data with all domains of the MDS‐NMS ( n  = 349), the Comparative Fit Index was ≥0.90 for the nine eligible domains. Missing data were negligible and moderate floor effect (42.90%) was found for the Non‐Motor Fluctuations subscale. Item homogeneity coefficient was adequate, and the correlation of the MDS‐NMS domains with other measures for related constructs was acceptable ( r s ≥ 0.50). Conclusions: The Spanish version of the MDS‐NMS followed the IPMDS Translation Program protocol, reached the criterion to be designated as an Official Translation, and is now available on the MDS website.